2005
DOI: 10.1103/physrevlett.94.108101
|View full text |Cite
|
Sign up to set email alerts
|

Short-Range Spectroscopic Ruler Based on a Single-Molecule Optical Switch

Abstract: We demonstrate a novel all-optical switch consisting of two molecules: a primary fluorophore that can be switched between its fluorescent and dark states by light of different wavelengths, and a secondary chromophore that facilitates switching. The interaction between the two molecules exhibits a distance dependence much steeper than that of Förster resonance energy transfer. This enables the switch to act as a ruler with the capability to probe distances difficult to access by other spectroscopic methods, thu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
349
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(365 citation statements)
references
References 30 publications
12
349
2
2
Order By: Relevance
“…EIT involves at least three levels and naturally three-level atoms are used in most cases. However, proper three-level structures are not available in some optical systems, such as in atomic nuclei [11][12][13] and biological fluorescent molecules [14], in which EIT can have important applications once realized. Interestingly, it has been shown that even with only two-level systems, EIT-like spectra can be achieved by locally addressing the atomic ensembles [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…EIT involves at least three levels and naturally three-level atoms are used in most cases. However, proper three-level structures are not available in some optical systems, such as in atomic nuclei [11][12][13] and biological fluorescent molecules [14], in which EIT can have important applications once realized. Interestingly, it has been shown that even with only two-level systems, EIT-like spectra can be achieved by locally addressing the atomic ensembles [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…2 (c)). In this case, optical switching can be produced by the throughput of a single off-resonant beam [6], [7]. d) Distance dependence: Owing to the (R) −6 distance dependence on the total transfer rate [3], lower relative Laser intensity (Wm -2 )…”
Section: (A) (D) the Results Demonstrate That Even For Moderate Lasmentioning
confidence: 99%
“…However, that number still suffices for a ten-fold resolution enhancement, and FPs are easier to use and ideally suited for in vivo experiments because they are expressed by the cell itself (Hess et al 2007;Shroff et al 2008). Synthetic dyes, by contrast, require specific buffer conditions involving high concentrations of reductants for photoswitching, and additional labeling procedures that limit their application to fixed specimens (Bates et al 2005;Heilemann et al 2005). PALM with independently running acquisition (PALMIRA) ) is a simplified version of PALM that uses only a single laser line, and direct STORM (dSTORM) is a simplified version of STORM that avoids the second dye molecule for activation (Heilemann et al 2008).…”
Section: Localization-based Super-resolution Microscopymentioning
confidence: 99%
“…In general, synthetic dyes are more photostable than fluorescent proteins and, therefore, provide a higher localization precision. For example, ∼6,000 photons per molecule were reported per switching cycle using the photoswitchable fluorophore pair Cy3-Cy5 (Bates et al 2005(Bates et al , 2007, whereas tdEosFP, one of the brightest PAFPs for PALM imaging, yields only ∼2,600 photons per molecule (Shroff et al 2007), and monomeric FPs often only a few hundred photons (Fuchs et al 2010). However, that number still suffices for a ten-fold resolution enhancement, and FPs are easier to use and ideally suited for in vivo experiments because they are expressed by the cell itself (Hess et al 2007;Shroff et al 2008).…”
Section: Localization-based Super-resolution Microscopymentioning
confidence: 99%